Pervaporative Removal of Propylene Glycol Monomethyl Ether from Water Using Polydimethyl siloxane Membranes Filled with SiO2 - Li, Q.; Sun, Y.; Zhang, X.Y.; Deng, X.H. (Asian Journal of Chemistry, 2011)
Polydimethyl siloxane (PDMS) membranes filled with nano-silicon dioxide (nano-silica) were prepared for pervaporative removal of propylene glycol monomethyl ether (PGME) from water. The structure of the filled and unfilled membranes was observed by scanning electron microscopy (SEM). The fourier transform infrared spectroscopy analysis (FTIR) revealed that only a little SiO2 reacted with PDMS, while most of SiO2 and PDMS were mixed physically. The experiment results of pervaporative removal showed that the methyl block RTV 103 (103-PDMS) membrane presented better separation performance than the methyl RTV 107 (107-PDMS) membrane. With increasing content of SiO2, separation factor increased firstly and then decreased for both 103 (103-PDMS) membranes and 107 (103-PDMS) membranes, whereas permeation flux increased continuously. When the addition of SiO2 was 1.2 wt % (based on PDMS component), the two kinds of membranes possessed the best separation performance.